Non-mycosis fungoides cutaneous lymphomas in a referral center in Taiwan: A retrospective case series and literature review - Liu, Kwei-Lan (PLoS One, 2020)
BACKGROUND: While mycosis fungoides (MF) and Sézary syndrome (SS) are the most common cutaneous lymphomas (CLs), there is limited data about non-MF/SS CLs. OBJECTIVE: We aimed to evaluate clinical characteristics of non-MF/SS CLs. METHODS: A retrospective analysis evaluated patients with non-MF/SS CLs covering a period of 17 years. The records of 59 patients with non-MF/SS CLs were reviewed for demographic profiles, clinical features, and survival outcomes. RESULTS: Our series consisted of 38 non-MF/SS cutaneous T-cell lymphomas (CTCLs) and 21 cutaneous B-cell lymphomas (CBCLs). In the group of non-MF/SS CTCLs including 33 primary and five secondary cases, there were cases of anaplastic large cell lymphoma (15.3% of non-MF/SS CLs), extranodal natural killer/ T-cell lymphoma (13.5%), peripheral T-cell lymphoma, not otherwise specified (13,5%), adult T-cell leukemia/lymphoma (8.5%), subcutaneous panniculitis-like T-cell lymphoma (6.8%) and angioimmunoblastic T-cell lymphoma (6.8%). In the group of CBCLs including nine primary and 12 secondary cases, there were cases of diffuse large B-cell lymphoma (22.0%), mantle cell lymphoma (5.1%), extranodal marginal lymphoma of mucosa associated lymphoid tissue (3.4%), follicle center lymphoma (3.4%) and intravascular large B-cell lymphoma (1.7%). The overall survivals were 57 months for non-MF/SS CTCLs and 41.5 months for CBCLs. Elevated serum lactate dehydrogenase level, thrombocytopenia, multiple anatomical sites of skin involvement and lower albumin level may be associated with poor prognosis in non-MF/SS CTCLs, but the latter two were not in CBCLs. CONCLUSION: With this series, we hope to provide indigenous data and outcome of non-MF/SS CLs. The overall survival of non-MF/SS CTCLs was better than CBCLs.